A SEROLOGICAL SURVEY OF ANTI-DENGUE ANTIBODY, JAMNAGAR, GUJARAT, INDIA - Patel, Nilesh D.; Teli, Chirag M. (Medico Research Chronicles, 2015)
Introduction: Dengue virus infection, the most important emerging tropical viral disease, is a significant cause of morbidity and mortality in many parts of the world like South-East Asia, Central and South America, and more than 200 countries all over continents. Epidemic outbreaks of dengue fever have become very frequent in recent years in India. Material and Method: A serological survey to detect IgM and IgG antibody to dengue virus was carried out on fever patients at Shri M. P. Shah Medical College, Jamnagar, Gujarat. A total of 245 febrile patients were included in this research.Result: 45 patients were diagnosed positive for malaria; hence they were not tested for dengue. Rest 200 patients were tested for dengue. 16 patients showed a positive titer of anti-dengue IgG antibody, with the overall seroprevalence of anti-dengue IgG at 8%. Out of 16 IgG positive cases, 11 (69%) patients lived in Jamnagar city and 5 (31%) patients belonged to rural areas around Jamnagar. No patient had shown a positive titer of anti-dengue IgM antibody.Conclusion: Overall 8% seropositivity for anti-dengue IgG antibody may be an alarming signal for dengue fever occurrence, although Jamnagar is not a known epidemic zone for dengue virus infection.